“Writing is challenging”: factors contributing to undergraduate students’ difficulties in writing English essays - Tri Nurilah Febriani (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
Essay writing is one of writing skills that must be mastered by students especially college ones because they often get an assignment to write an essay. However, many students find it difficult when they are assigned to compose an essay. This research aims to investigate the difficulties in English essay writing and its factors. Framed in a narrative inquiry, 33 students and one lecturer volunteered to participate. Data were collected through open-ended questionnaires and semi-structured interviews. The data were analyzed using thematic analysis by Braun and Clarke. Study findings reveal that students find difficulties in grammar, vocabulary, cohesion and coherence, and developing topic ideas. Factors that contribute to students’ difficulties are both internal factors (psychological factors and linguistic factors) and external factors (peer support and advisor support). Several ways that students do to overcome the difficulties in writing essays were motivating themselves, studying and reading a lot, and writing practice. In addition, they were also asked their friends and their lecturer to get more explanation. To make a good essay, students need to improve their grammar and punctuation ability. They, likewise, need to increase their logical thinking ability to create coherent and cohesive essays.